2016
DOI: 10.1515/ijamh-2016-0069
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of online versus live multi-family psychoeducation group therapy for children and adolescents with mood or anxiety disorders: a pilot study

Abstract: Online MFPGT may be an effective way to increase knowledge, provide resources and support and build on skills thus giving individuals more control and confidence when dealing with a mood or anxiety disorder while on a waitlist. MFPGT showed equal efficacy in live and online groups, indicating that the online program has the potential to be a more convenient and accessible program for families. More research is needed with a greater sample size.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 8 publications
1
37
0
1
Order By: Relevance
“…Studies on technologies for depression also varied in quality: 10 studies were of excellent quality [ 56 , 57 , 59 , 63 - 67 , 71 , 81 ], 2 were of very good quality [ 60 , 68 ], 4 were of moderate quality [ 58 , 61 , 69 , 72 ], and 2 were of low quality and received a score of 25 [ 62 ] and 0 [ 70 ]. Studies evaluating technologies applicable to both anxiety and depression were of excellent [ 75 , 77 ], very good [ 74 ], and moderate [ 73 , 76 ] quality. The most common factors impacting the quality scores for quantitative studies were the lack of description on how randomization sequences were generated and if/how allocation was concealed (ie, see MMAT items 2.1 and 2.2 in Multimedia Appendix 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies on technologies for depression also varied in quality: 10 studies were of excellent quality [ 56 , 57 , 59 , 63 - 67 , 71 , 81 ], 2 were of very good quality [ 60 , 68 ], 4 were of moderate quality [ 58 , 61 , 69 , 72 ], and 2 were of low quality and received a score of 25 [ 62 ] and 0 [ 70 ]. Studies evaluating technologies applicable to both anxiety and depression were of excellent [ 75 , 77 ], very good [ 74 ], and moderate [ 73 , 76 ] quality. The most common factors impacting the quality scores for quantitative studies were the lack of description on how randomization sequences were generated and if/how allocation was concealed (ie, see MMAT items 2.1 and 2.2 in Multimedia Appendix 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…All 5 studies examined the acceptability of technologies aimed at treating anxiety and depression. Of these, 3 (60%) reported high satisfaction [ 73 - 75 ], with children and parents describing that they would not change any aspects of the program, and 2 studies (40%) reported moderate satisfaction [ 76 , 77 ]. Two studies examined adoption and reported low adherence to program sessions [ 75 ] and high website usage rates [ 77 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A community‐based implementation of this treatment modality confirmed its effectiveness in practice settings (McPherson et al ., ). Finally, a recent pilot study (Sapru et al ., ) showed that online psychoeducational MFT was as efficient, in terms of knowledge acquisition and family EE, as live MFT for children (≤ 12 years) with mood and anxiety disorders, suggesting online MFT is a convenient and accessible alternative for families.…”
Section: Mood Disordersmentioning
confidence: 99%
“…Anxiety disorders, estimated to affect 10-20% of adolescents, are the most prevalent mental health disorders in youth and often predate depression (Costello, Egger, & Angold, 2005;Essau, Lewinsohn, Olaya, & Seeley, 2014;Merikangas et al, 2010;Sapru et al, 2016;Wittchen, Kessler, Pfister, Höfler, & Lieb, 2000). These disorders are associated with low self-esteem, poor problem solving skills, social inhibition, and a strong desire to be accepted (Anderson, Williams, McGee, & Silva, 1987;Khalid-Khan, Santibanez, McMicken, & Rynn, 2007;McGee et al, 1990;Twenge, 2000).…”
Section: Introductionmentioning
confidence: 99%